2022
DOI: 10.1007/s40262-022-01125-2
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of Population Pharmacokinetic Analyses of Linezolid

Abstract: In recent years, many studies on population pharmacokinetics of linezolid have been conducted. This comprehensive review aimed to summarize population pharmacokinetic models of linezolid, by focusing on dosage optimization to maximize the probability of attaining a certain pharmacokinetic-pharmacodynamic parameter in special populations. We searched the PubMed and EMBASE databases for population pharmacokinetic analyses of linezolid using a parametric non-linear mixed-effect approach, including both observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 107 publications
2
20
0
Order By: Relevance
“…We have demonstrated that a larger trough level was reached when the daily dosage of LZD is 600 mg. There was also a difference in clearance of LZD, from the 8th to 16th week, and this could be due to alterations in renal function with the continued use of LZD, as noticed by other investigators [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 56%
“…We have demonstrated that a larger trough level was reached when the daily dosage of LZD is 600 mg. There was also a difference in clearance of LZD, from the 8th to 16th week, and this could be due to alterations in renal function with the continued use of LZD, as noticed by other investigators [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 56%
“…The ratio of the area under the drug plasma concentration–time curve over 24 h to the MIC (AUC/MIC) or percentage time above the MIC (%T > MIC) are predictors of the therapeutic response, and concentrations in the range of 2–8 mcg/mL appear to define the optimal window for acute bacterial infections, while a cut-off value >8 mg/L is an indicator for thrombocytopenia. Thus, TDM based on PK models or continuous infusion over 6 h instead of intermittent infusion is recommended for the optimization of Linezolid treatment to achieve the target AUC/MIC [ 17 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Created by the author (DM) with the antibiotic concentration that would inhibit the growth of 90% of tested bacterial isolates (MIC90) and minimal inhibitory concentration (MIC) range adapted from Kucers' The Use of Antibiotics. 14 certain clinical conditions are associated with linezolid underexposure and an increased risk of treatment failure. These include obesity, augmented renal clearance (ARC), critical illness, and/or the presence of concomitant medications, such as rifampicin.…”
Section: Dosage Adjustmentmentioning
confidence: 99%
“…A recently published review of the population pharmacokinetics of linezolid reported a residual PK variability of nearly 20%. 14…”
Section: A Brief Introduction To Linezolid An Increasingly Important ...mentioning
confidence: 99%